Association of Systemic Arterial Properties With Right Ventricular Morphology: The Multi‐Ethnic Study of Atherosclerosis (MESA)‐Right Ventricle Study. Issue 12 (23rd November 2016) - Al‐Naamani, Nadine; Chirinos, Julio A.; Zamani, Payman; Ruthazer, Robin; Paulus, Jessica K.; Roberts, Kari E.; Barr, R. Graham; Lima, Joao A.; Bluemke, David A.; Kronmal, Richard; Kawut, Steven M.
Abstract : Background: Systemic arterial stiffness is recognized as a major contributor to development of left ventricular dysfunction and failure; however, the relationship of systemic arterial properties and the right ventricle (RV) is unknown. Methods and Results: The associations between systemic arterial measures (total arterial compliance [TAC], systemic vascular resistance [SVR], and aortic augmentation index [AI]) and RV morphology (mass, end‐systolic [RVESV] and end‐diastolic volume [RVEDV], and ejection fraction [RVEF]) were examined using data from the Multi‐Ethnic Study of Atherosclerosis. All analyses were adjusted for anthropometric, demographic, and clinical variables and the corresponding left ventricular parameter. A total of 3842 subjects without clinical cardiovascular disease were included with a mean age of 61 years, 48% male, 39% non‐Hispanic white, 25% Chinese‐American, 23% Hispanic, and 13% black. RV measures were within normal range for age and sex. A 1‐mL/mm Hg decrease in TAC was associated with 3.9‐mL smaller RVESV, 7.6‐mL smaller RVEDV, and 2.4‐g lower RV mass. A 5‐Wood‐unit increase in SVR was associated with 0.6‐mL decrease in RVESV, 1.7‐mL decrease in RVEDV, and 0.4‐g decrease in RV mass. A 1% increase in AI was associated with 0.2‐mL decrease in RVEDV. We found significant effect modification by age, sex, and race for some of these relationships, with males, whites, and younger individuals having greater decreases in RV volumes and mass. Conclusions: Markers of increased systemic arterial load were associated with smaller RV volumes and lower RV mass in a population of adults without clinical cardiovascular disease.